Increased sexual arousal in patients with movement disorders - Teive, Hélio A. G.; Moro, Adriana; Moscovich, Mariana; Munhoz, Renato P. (Arquivos de Neuro-Psiquiatria, 2016)
Increased of sexual arousal (ISA) has been described in different neurological diseases. The purpose of this study was present a case series of ISA in patients with movement disorders.Method Fifteen patients with different forms of movement disorders (Parkinson’s disease, Huntington’s disease, Tourette´s syndrome, spinocerebellar ataxia type 3), were evaluated in the Movement Disorders Unit of the Federal University of Paraná.Results Among Parkinson’s disease patients there were seven cases with different forms of ISA due to dopaminergic agonist use, levodopa abuse, and deep brain stimulation (DBS). In the group with hyperkinetic disorders, two patients with Huntington’s disease, two with Tourette’s syndrome, and four with spinocerebellar ataxia type 3 presented with ISA.Conclusions ISA in this group of patients had different etiologies, predominantly related to dopaminergic treatment or DBS in Parkinson’s disease, part of the background clinical picture in Huntington’s disease and Tourette’s syndrome, and probably associated with cultural aspects in patients with spinocerebellar ataxia type 3.
Keywords: hypersexual disorder; increased of sexual arousal; hypersexuality; movement disorders